From Influence To Intention: The Effect Of Social Media Influencers On Gen Z’s E-Commerce Purchasing Decision - Adji Karlita Shavira (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
Digitalization has changed how consumers engage with information and shop online. In this context, the significance of influencers as public figures on social media is growing ever more vital, particularly for Generation Z who are very adept with technology. Nonetheless, a knowledge gap exists regarding the impact of influencer credibility and engagement tactics on consumer purchasing decisions on e-commerce platforms like Tokopedia. This study takes a qualitative approach with a literature review designed to comprehend Generation Z's attitude toward influencers and their influence on consumer behavior. The results show that the credibility of influencers, including aspects of expertise, trust, and attractiveness, is an important factor in establishing emotional bonds with consumers that influence purchasing behavior. Two-way communication strategies in the form of digital interactions, such as comments, live streaming, and interactive content, have been shown to increase consumer engagement and promotion efficacy. Generation Z is more responsive to influencers who are authentic and whose values align with the product being promoted than to official promotion techniques. Hence, this study suggests that business practitioners and educators consider influencer credibility and interactive strategies in building significant communication.